The canon a whirligig tour of the beautiful basics of science - Angier, Natalie (Boston Houghton Mifflin Company, 2007)
Award-winning science journalist Angier takes us on a "guided twirligig through the scientific canon." She draws on conversations with hundreds of the world's top scientists, and her own work as a reporter for the New York Times, to create an entertaining guide to scientific literacy--a joyride through the major scientific disciplines: physics, chemistry, biology, geology, and astronomy. It's for anyone who wants to understand the great issues of our time--from stem cells and bird flu to evolution and global warming. It's also one of those rare books that reignites our childhood delight in figuring out how things work: we learn what's actually happening when our ice cream melts or our coffee gets cold, what our liver cells do when we eat a caramel, how the horse shows evolution at work, and that we really are all made of stardust.--From publisher description.
Includes bibliographical references (p. [267]-279) and index.
Tac-3561g donated by Dr. Victorio N. Sugbo.
Keywords: Science -- Popular works